Early labour midwifery care in Italy: local and cross-cultural challenges - Iannuzzi, Laura; Borrelli, Sara E. (Royal College of Midwives, 2014)
INTRODUCTION. The definition of early labour and its management are debatable issues at a local, national and international level. In Italy, this issue is also of concern. APPROACH. This is a descriptive discussion paper designed to portray the cross-cultural issues and the comparisons between Italian and international early labour care. KEY ISSUES. Many of the issues regarding early labour care in Italy resonate with what emerged from the international literature. These include the dilemmas of diagnosis and management of early labour, appropriate timing for women’s admission to hospitals in the latent phase and the type of maternity service available to women in early labour. The lack of a mapping of the geographically variable services offered to women in the Italian peninsula makes the task of offering national data to international research on early labour care challenging as little is known about the availability, efficiency and effectiveness of triage systems for women in the latent phase of labour. THE WAY FORWARD. The organisation of maternity services within the Italian national health system requires a review to consider how best to meet women’s needs during early labour. Research in this field needs to be carried out in Italian birthing settings in order to be able to understand what would work best for women within the specific socio-cultural context and what is required to enhance midwifery knowledge and skill.